The results of physical rehabilitation of football players of 18-24 years old after injuries of the ankle joint - Charbel, Y.; Podkopai, T.; Podkopa, D. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to improve the results of physical rehabilitation of football players of 18-24 years old with intra-articular injuries of the ankle joint at the outpatient stage by optimizing and improving the effectiveness of differentiated application of rehabilitation measures involved in the training process. Material and methods: this work was based on the results of observation of 36 football players, conducted at the clinic of the Medical Center "Mir Majid Erslan" in Beirut (Lebanon). We evaluated the effectiveness of physical rehabilitation: according to the scales LEFS, VAS, according to the questionnaire Euro Qol - 5D, according to the methods of A.V. Kalashnikov and NEER. Results: these studies indicate that with a positive dynamics of changes in the functional state of the injured in both clinical groups, more pronounced and significantly better are the results obtained in the injured main group, who underwent physical rehabilitation according to our proposed program. Conclusions: the analysis of the results of the study showed that with the positive dynamics of changes in the functional state of the injured both clinical groups more pronounced and significantly better results were obtained in the injured main group, who underwent physical rehabilitation according to the proposed program. In addition, the injured in the main group at the same time and volume of observation, these indicators were better than in the control group.